Mon’ Amie Printing Service business / Afifah Athirah Saini ... [et. al] - Saini, Afifah Athirah; Glifton, Clarissa Eleanor; Bainon, Nadine Drew-Ann; Salam, Nur Atikah; Basuni, Muhammad Azizi (2019)
Mon’ Amie Printing Services is a business enterprise that will operate a standard business services firm. Although our business services centre will be based in Desa Ilmu, Kota Samarahan where we have been able to secure a standard office facility that is ideal for the kind of business we want to pursue. We have plans and choose to spread this business across the state of Kota Samarahan with smaller kiosk - like printing shops strategically positioned in key areas which we aimed for offices, shop houses, educational institution and many more.